Anatomy and Adaptations of the Chewing Muscles in Daubentonia (Lemuriformes). Issue 2 (13th December 2013) - Perry, Jonathan M. G.; Macneill, Kristen E.; Heckler, Amanda L.; Rakotoarisoa, Gilbert; Hartstone‐Rose, Adam
ABSTRACT The extractive foraging behavior in aye‐ayes (Daubentonia madagascariensis) is unique among primates and likely has led to selection for a specialized jaw adductor musculature. Although this musculature has previously been examined in a subadult, until now, no one has reported the fascicle length, weight, and physiological cross‐sectional area (PCSA) for these muscles in an adult aye‐aye specimen. For the present study, we dissected an adult wild‐born aye‐aye from the Tsimbazaza Botanical and Zoological Park, Antananarivo, Madagascar. The aye‐aye follows the general strepsirrhine pattern in its overall jaw adductor muscle anatomy, but has very large muscles and PCSA relative to body size. Fascicle length is also relatively great, but not nearly as much as in the juvenile aye‐aye previously dissected. Perhaps chewing muscle fascicles begin relatively long, but shorten through use and growth as connective tissue sheets expand and allow for pinnation and increased PCSA. Alternately, it may be that aye‐ayes develop fascicular adaptation to wide gapes early in ontogeny, only to increase PCSA through later development into adulthood. The functional demands related to their distinctive manner of extractive foraging are likely responsible for the great PCSA in the jaw adductor muscles of the adult aye‐aye. It may be that great jaw adductor PCSA in the adult, as compared to the juvenile, is a means of increasing foraging efficiency in the absence of parental assistance. Anat Rec, 297:308–316, 2014. © 2013 Wiley Periodicals, Inc.